Pebax composite hollow fiber membranes by modulating PDMS surface hydrophilicity and coatability for CO2 capture - Qing-Yun Chou; Yueh-Han Huang; James J.J. Hwang; Hui-Hsin Tseng; Juin-Yih Lai; Tai-Shung Chung (Carbon Capture Science & Technology)
Eco-friendly CO2 capture technologies are essential to minimize global warming. In this study, the fundamentals of designing and fabricating composite hollow fiber membranes consisting of an inner polyethersulfone (PES) substrate, a polydimethylsiloxane (PDMS) gutter layer, and an outer Pebax selective layer were revealed for CO2/N2 separation. The resultant Pebax/PDMS/PES composite hollow fiber membranes possess a CO2 permeance of 1253 GPU and an ideal CO2/N2 selectivity of 34.9 at 0.1 MPa and 25 °C. They have a comparable CO2/N2 selectivity but a much higher CO2 permeance of 1–2 times than other Pebax based composite hollow fiber membranes in literature. The much higher CO2 permeance demonstrates the effectiveness of the proposed strategies to design multi-layer composite hollow fiber membranes for CO2 capture. Two major challenges have been innovatively overcome when developing these composite membranes. Namely, the diminish of PDMS intrusion during its coating on PES substrates and the hydrophilization of inherently hydrophobic PDMS surfaces for the Pebax coating. The former was solved by optimizing the spinning conditions such as air gap distance, coagulation temperature, and bore fluid composition to design the substrates with a dense outer surface and a porous inner surface, thus minimizing PDMS intrusion and gas transport resistance. The latter was overcome using plasma to improve the wettability of PDMS surfaces. The optimal Pebax/PDMS/PES membranes also have stable mixed gas performance using an N2/CO2 feed of 85/15 (mol/mol %) at 0.2 MPa and 25 °C over one month, achieving a CO2 permeance of 829 GPU and a CO2/N2 selectivity of 32.5.